INOVASI PEMBELAJARAN (TEACHING GRANT) TERINTEGRASI APLIKASI ADOBE FLASH C.S.6 UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS - Susanti, Nova; Dani, Rahma (EduFisika: Jurnal Pendidikan Fisika, 2023)
The activity of students when attending Astronomy and Geophysics Lectures in the physics education study program so far is still lacking. This is because the lecture tools are inadequate, students only listen to explanations from lecturers, and learning through the Zoom application is not very effective for students. To overcome this problem, it is necessary efforts are made to design Learning Designs that are good and adequate so that lectures can improve critical thinking skills. This study aimed to design a Learning Design with Adobe Flash C.S.6 Applications. The developer method of this research is 4-D (Four-D mode). The product development stage in this model is the definition stage, the design stage, the development stage, and the dissemination. From the results of the study, it can be concluded that the learning device is feasible to use.